Implementation of the Cooperative Learning Model Using the Make a Match Method to Improve Fiqh Learning Skills in Students of MTs Al-Irsyad 07 Batu City - Nabil, Wildan; Bashith, Abdul; Zuhriyah, Indah Aminatuz (AS-SABIQUN, 2025)
This study investigates the implementation of the Make a Match cooperative learning model to address low student performance in the Fiqh subject at MTs Al-Irsyad 07 Batu, where 28% of students scored below the minimum competency threshold (KKM), largely due to the density of reading material. The research aims to explore the planning, implementation, and evaluation processes of the learning model, as well as the supporting and inhibiting factors influencing its effectiveness. Adopting a qualitative approach, data were collected through observation, interviews, and documentation involving the Head of Madrasah, Deputy for Curriculum, Fiqh teachers, and students. Data were analyzed using an interactive model comprising data reduction, data display, and conclusion drawing. The findings indicate that the planning process includes formulating learning objectives, selecting relevant materials, and preparing appropriate teaching strategies. Implementation occurs in three phases: preparation, instruction, and closure. Evaluation encompasses cognitive, affective, and psychomotor domains. The study concludes that the Make a Match method fosters an engaging learning environment that enhances students’ motivation and learning skills in Fiqh. The findings suggest that employing varied and interactive instructional strategies can improve learning outcomes and create a more dynamic classroom experience. These results offer practical implications for educators seeking to enhance instructional quality and student engagement in religious education.